Diel timing of migration is not plastic in a migratory ungulate. (October 2022) - Jakopak, Rhiannon P.; Sawyer, Hall; LaSharr, Tayler N.; Randall, Jill; Dwinnell, Samantha P.H.; Fralick, Gary L.; Monteith, Kevin L.
Abstract : The temporal windows during which animals complete essential life processes (i.e. temporal niche) allow animals to match their actions to a given environmental context. When completing seasonal migrations, some migrants switch their activity patterns (e.g. from diurnal to nocturnal in multiple species of migratory birds) to take advantage of better conditions. We tested the temporal niche-switch hypothesis by comparing activity patterns before and during migration for four populations of migratory mule deer, Odocoileus hemionus, in western Wyoming, U.S.A. (2007–2019). We predicted that the physically taxing and risky event of terrestrial migration would prompt shifts in diel activity patterns. In contrast to the niche-switch hypothesis, mule deer did not drastically change their activity patterns during migration. Both before and during migration, mule deer were crepuscular (i.e. most active during twilight hours). When migrating in the spring, however, mule deer tended to concentrate activity near dawn, although they did not concentrate activity near dawn in the autumn, when less snow was present. By moving in the morning during spring migration, mule deer moved when snow was hardest, potentially allowing them to avoid the energetic costs of sinking into deep snow. Mule deer overall maintained a consistent pattern of crepuscular activity, but fine-tuned their activity patterns during migration, which may allow them to better match their behaviours with environmental conditions while completing an important life event. Rather than abandoning activity patterns, animals instead may make subtle alterations in their activity patterns to take advantage of present conditions. Highlights: Mule deer did not switch the time of day that they were most active when migrating. Instead, migratory mule deer fine-tuned their migratory behaviour. Shifts in temporal niches may be underappreciated behavioural strategies.